The World Bank's Involvement in Global and Regional Partnership Programs : An Independent Assessment - Independent Evaluation Group (Washington, DC: World Bank, 2015)
Programs with regional or global reach are increasingly being used to channel funds to specific development needs, reflecting the emergence of new funding sources and in some cases donor distrust of the established multilateral development model to deliver global goods. Evaluating the contribution of these programs is important to understanding whether their relevance and effectiveness live up to their promise and how they contribute to the new aid architecture. This is third biennial report of the Independent Evaluation Group (IEG) on the World Bankapos;s involvement in global and regional partnership programs (GRPPs) since the conclusion of IEGapos;s two-phase evaluation on this topic in 2004. The first two biennial reports were discussed at the committee on development effectiveness subcommittee in May 2006 and March 2008. The present report is the first one that will be disclosed to the public reflecting the growing maturity of this line of IEG's work. This report has been based on the first 17 GPRs that IEG has completed and on interviews with Bank staff who have been involved in the management and oversight of GRPPs in central, network, and regional Vice Presidencies. IEG greatly appreciates the time and insights provided by those interviewed for this report, including network and regional staff who confirmed the accuracy of the basic information provided in the appendixes to this report on the nearly 120 GRPPs with which the Bank is currently involved. The objectives of the 17 programs that IEG has reviewed in depth since 2006 have been highly relevant in terms of collectively addressing important global and regional issues, but few have had a well-articulated results framework. Almost all programs can point to some positive achievements in terms of outputs. However, the sustainability of a number of programs and the benefits they foster is threatened by weak resource mobilization strategies, failure to keep up with the changing global and regional context, and difficulties in demonstrating results at the outcome level.